Methylation of melatonin receptors in patients with unipolar and bipolar depression. (April 2023) - Lesicka, Monika; Dmitrzak-Weglarz, Monika; Jablonska, Ewa; Wieczorek, Edyta; Kapelski, Pawel; Szczepankiewicz, Aleksandra; Pawlak, Joanna; Reszka, Edyta
Abstract: Disturbances of melatonin secretion alter the circadian rhythm and sleep-wake cycle, which is observed among patients with depression. Melatonin acts via melatonin receptors MT1 and MT2, which are present in many tissues, including peripheral blood mononuclear cells (PBMC). We assume that disturbances of the melatonin pathway in the brain may be reflected by molecular changes in peripheral organs. The study objective was to evaluate the methylation profile of CpG island in the promoter region of melatonin receptor genes MTNR1A and MTNR1B in PBMC of patients with depression and compare it with healthy volunteers. The study group comprised 85 patients with unipolar (UP) and bipolar disorders (BP) and 83 controls. The methylation pattern of CpG island in the promoter region was analyzed using the quantitative methylation-specific real-time PCR (qMSP-PCR) method. We found that the methylation profile of the patients with depression varied in comparison to the control group. The methylation level of MTNR1A was significantly lower among depressed patients compared to controls. Additionally, melatonin concentration was negatively correlated with MTNR1B methylation level among the UP patients. The study may suggest that the methylation profile of melatonin receptors in PBMC may be used as a complementary molecular marker in depression diagnosis. Highlights: The epigenetic pattern of MTNR1A is altered among BP&UP patients compared to controls. Melatonin level decreases as MTNR1B methylation increases among UP patients. Sleep disturbances were associated with a different methylation pattern of MTNR1B .